Hubungan Pengetahuan dan Sikap tentang Antenatal Care (ANC) dengan Kunjungan ANC - Arisanti, Atika Zahria; Susilowati, Endang; Husniyah, Imamatul (Faletehan Health Journal, 2024)
Pregnant women at Mijen II Community Health Center, Demak Regency did not regularly attend antenatal care (ANC); although, they knew that ANC visits during pregnancy are important. Coverage of ANC visits by pregnant women to health workers is based on the standards of Health Ministry which have been set at a minimum of 6 times. The aim of the research was to determine the relationship between pregnant women's knowledge and attitudes about ANC and ANC visits. The type of research used was quantitative with cross-sectional design. The samples of this study were 39 respondents selected by using purposive sampling technique. Chi Square test was used to analyze the research data. The results of data analysis showed that there was no relationship between knowledge of pregnant women (p-value 0.176) and attitudes of pregnant women (p-value 0.060) with ANC visits. The results of survey with interviews to pregnant women showed that 80% of pregnant women did not do ANC regularly for reasons of being lazy, working, having no complaints, and having a poor economy. Health workers, especially midwives, were expected to further increase the screening of pregnant women, so they can achieve the target of 100% ANC visits by health workers. The screening should not only be done by waiting for mothers’ visit at community health center or integrated service post but by making home visits.